Anion inhibition studies of the Zn(II)-bound ι-carbonic anhydrase from the Gram-negative bacterium Burkholderia territorii - Andrea Petreni; Viviana De Luca; Andrea Scaloni; Alessio Nocentini; Clemente Capasso; Claudiu T. Supuran (Taylor & Francis Group, 2021)
Burkholderia territorii, a Gram-negative bacterium, encodes for the ι-class carbonic anhydrase (CA, EC 4.2.1.1) BteCAι, which was recently characterised. It acts as a good catalyst for the hydration of CO2 to bicarbonate and protons, with a kcat value of 3.0 × 105 s−1 and kcat/KM value of 3.9 × 107 M−1 s−1. No inhibition data on this new class of enzymes are available to date. We report here an anion and small molecules inhibition study of BteCAι, which we prove to be a zinc(II)- and not manganese(II)-containing enzyme, as reported for diatom ι-CAs. The best inhibitors were sulphamic acid, stannate, phenylarsonic acid, phenylboronic acid and sulfamide (KI values of 6.2-94 µM), whereas diethyldithiocarbamate, tellurate, selenate, bicarbonate and cyanate were submillimolar inhibitors (KI values of 0.71-0.94 mM). The halides (except iodide), thiocyanate, nitrite, nitrate, carbonate, bisulphite, sulphate, hydrogensulfide, peroxydisulfate, selenocyanate, fluorosulfonate and trithiocarbonate showed KI values in the range of 3.1-9.3 mM.